Zero-strain Ca0.4Ce0.6VO4 anode material for high capacity and long-life Na-ion batteries. Issue 45 (15th November 2021) - Liang, Guisheng; Xiong, Xuhui; Yang, Liting; Liu, Xianhu; Che, Renchao
Abstract : Sodium-ion batteries (SIBs) have attracted widespread attention for grid-scale energy storage owing to the natural abundance of sodium, low cost and environmental friendliness. Abstract : Sodium-ion batteries (SIBs) have attracted widespread attention for grid-scale energy storage owing to the natural abundance of sodium, low cost and environmental friendliness. Generally, the electrochemical performances of SIBs are largely determined by the electrode materials. However, the development of electrode materials with long-term stability and large capacity remains a great challenge. Here, we exploited a tetragonal-type Ca–Ce–V–O compound (Ca–CeVO4 ) with a robust framework for stable Na + storage, which exhibits exceptional cycling stability ( ca. 97.8% capacity retention for 2000 cycles) and a reversible capacity of about 170 mA h g −1 with a safe average storage potential of ∼0.73 V ( vs. Na + /Na). The crystal structure of Ca–CeVO4 contains large-sized quadrilateral channels (∼3.6 Å), which provide a larger number of vacancies for Na + insertion, thus resulting in a large theoretical capacity. The tiny unit-cell volume change (0.53%) of Ca–CeVO4 in the sodiation/desodiation process can effectively release the mechanical stress induced by Na + insertion/deinsertion, which is responsible for the excellent long-term cycle life of Ca–CeVO4 . This work will make a contribution to the future design of stable electrode materials for long-life SIBs.